2015
DOI: 10.3390/polym7121534
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antibacterial Properties of Carrageenan and Gelatine Hydrosols and Hydrogels Incorporated with Acidic Electrolyzed Water

Abstract: Abstract:The article focuses on investigation of the effects of usage of acidic electrolyzed water (AEW) with different sodium chloride concentration (0.001%, 0.01%, and 0.1%) for the preparation of carrageenan and gelatine hydrosols and hydrogels. To determine physiochemical properties of hydrosols, the pH, oxidation-reduction potential (ORP), available chloride concentration (ACC) and rheological parameters such us gelation and flow temperatures were measured. The samples were also characterized using Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…The characteristics of physicochemical properties of the prepared carrageenan and gelatine hydrosols are presented in the work of Brychcy et al . (). It was decided to use only variants of AEW with the highest level of ACC.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The characteristics of physicochemical properties of the prepared carrageenan and gelatine hydrosols are presented in the work of Brychcy et al . (). It was decided to use only variants of AEW with the highest level of ACC.…”
Section: Resultsmentioning
confidence: 97%
“…() and Brychcy et al . (). The results clearly indicate that the hydrosols containing AEW are more effective in inactivating surface microbiota than others with sodium chloride solution at the same concentration level.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest values of EC were noticed for N0 variants (2.15–2.28 mS/cm) and the highest were measured for samples with 0.2% NaCl (5.41–5.55 mS/cm). The ACC concentration depends on the current density and sodium chloride values [24,25]. The results showed that changing the current from 200 to 400 mA caused an increase in ACC concentration from 9.53 to 13.96 mg/L for the sample with 0.1% NaCl and from 11.30 to 19.72 mg/L for the N0.2 variant.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of the population of all three pathogens by approximately 7 log CFU/mL was obtained after 5 min of treatment, while complete inactivation was noticed after 10 min of exposure. Brychcy et al [24] investigated the effects of hydrosols incorporated with EOW on E. coli and S. aureus strains. The highest reduction of S. aureus and E. coli was observed after treatment with carrageenan (1.80 and 1.59 log reduction, respectively) and gelatin (2.10 and 1.56 log reduction, respectively) hydrosols incorporated with 0.1% of electrolyzed saline solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation